Role of adenosine triphosphate and protein kinase A in the force-frequency relationship in isolated rat cardiomyocytes - Ozturk, Nihal; Erkan, Orhan; Uslu, Serkan; Ozdemir, Semir (Archives of Biological Sciences, 2023)
Paper description: There is insufficient information about the force-frequency relationship in isolated cardiomyocytes and the available information is contradictory. We investigated the force-frequency relationship in contraction and the reasons for the conflicting results. Contraction and Ca2+ transients were recorded at 1, 2, 4 Hz excitation frequencies. The increase in frequency caused a decrease in the amplitude of contraction, a prolongation of the relaxation time, a slowdown in the relaxation rate, and an increase in the diastolic Ca2+ Energy deficiency and lack of β-adrenergic system regulation may play a role in these changes. Abstract: The physiological heart rate of rodents is around 4-6 Hz, although a stimulus frequency of 1 Hz is generally used in isolated cardiomyocytes to study changes in the contraction-relaxation cycle in cardiac muscle physiology and pathophysiology. Our study investigated the contraction parameters in isolated cardiomyocytes at 1, 2 and 4 Hz stimulation, and the roles of ATP and protein kinase A (PKA) in the force-frequency relationship in isolated cardiomyocytes. The contraction of the cell and intracellular Ca2+ changes were recorded simultaneously during cell stimulation by applying pulses of 6-8 V amplitude with frequencies of 1, 2 and 4 Hz. The increase in stimulus frequency caused a significant decrease in the percentage of shortening, relaxation times, slowing of the relaxation rate, and a significant increase in diastolic Ca2+ levels, but had no effect on the contraction rate and Ca2+ transients. Administration of ATP and N6-benzoyladenosine-3ʹ-5ʹ-cyclic monophosphate (6-BNZ-cAMP) caused an increase in contraction amplitude and speed which were proportional to the stimulus frequency but had no effect on the relaxation times. The experimental results show that the force-stimulus frequency has a negative correlation in isolated myocytes and that energy metabolism and the β-adrenergic system may be responsible for this relationship.